The politics of sex trafficking: a moral geography - O'Brien, Erin E. (Critical criminological perspectives, 2013)
The politics of sex trafficking -- Perspectives and players -- Stories of trafficking -- Measuring trafficking -- Defining trafficking -- Causes of trafficking -- Silencing dissent -- A moral geography